OPTIMALISASI PRODUKSI REPAIR UNIT MOBIL CACAT PART DENGAN ELIMINASI WASTE MENGGUNAKAN LEAN MANUFACTURING - Abdurrahman, Rosyad Zaki; Sutrisno, Sutrisno (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
In the automotive industry, increasing competition requires companies to continuously optimize production processes to enhance quality and efficiency. PT. XYZ faces issues in the repair process of units with defective parts, causing production delays and unmet daily targets. This research aims to identify and eliminate waste occurring in the production process, particularly waste delays, by applying the Lean Manufacturing concept. The methods used are Value Stream Mapping (VSM) and Fishbone Diagrams to analyze process flow and identify the root causes of waste. Primary data were obtained through direct observation and interviews with relevant parties at PT. XYZ, while secondary data consisted of historical production records.The research results indicate that the most significant waste delays occur in the repair unit for vehicles with defective parts, caused by insufficient manpower, material delays, and suboptimal machine performance. Through improvement suggestions based on the 5W+1H analysis, PT. XYZ is expected to reduce time waste, improve production efficiency, and meet the set daily production targets. The application of Lean Manufacturing has proven effective in helping the company identify and address waste issues in the production process.